Feeling Bodies: Embodying Psychology - Cromby, John. author. aut Link
X, 221 p.
Keywords: Before we are anything else, we are feeling bodies. In fact, feelings are an important part of every experience we ever have. This book explains what feelings are, describes their relationship with other psychological phenomena, and shows how their analysis transforms understandings of some key topics related to health and illness.